MEASURING RISK MATURITY LEVEL IN XYZ BANK - Viona, Vincentia
Expansion and development of a company is affected by internal and external factors. One of the most crucial things to be concerned about is risk management, where uncertainty can bring positive and negative impact for the company itself. Nowadays, risk management in state-owned enterprises is fully intensified by the government through PER-2/MBU/03/2023 about State- Owned Corporation Guidance of Good Corporate Governance and Significant Corporation, which was PER-5/MBU/09/2022 about Risk Management in State-Owned Corporation beforewards. State-owned enterprises are mandatory to do regular risk maturity assessment, according to PER-01/MBU/2011. Focusing on banking, which is a highly regulated industry, risk management must be well implemented since it will impact on their performance and anticipate loss and failure. In Indonesia, this is a mandatory through Regulation of OJK 18/POJK.03/2016 about Risk Management Application for Commercial Banks and Regulation of BI 8/4/2006 about Good Corporate Governance Implementation. Risk maturity level, is a measurement where all aspects of risk management implementations, principles, and processes. A bank must do at least annual risk maturity assessment, according to Regulations of Otoritas Jasa Keuangan 11/POJK.03/2022 to develop and manage good organizational governance and implementation of risk management to avoid financial crisis. The average risk maturity level for financial industry, including banking, is level 5. Therefore, this research measures risk maturity level in XYZ Bank, one of the state-owned banks, with its aim to see implementations of all regulations related to risk management in bank and state-owned companies, determine its maturity level compared with industry level average, and give suggestions to the company in managing and improving their risk maturity level. This research focuses on assessment according to ISO 31000:2018 Risk Management Guidance, especially with elements in the Framework. All data was collected through quantitative method with questionnaire to all employees with 398 total respondents, qualitative method through interview with Risk Management Division, and secondary research with document availability scoring. Calculation methods used for this research are the weighting method, where all aspects for measurements are determined at first with categorization from ISO31000 framework and weighted based on discussion with experts and the company representatives; and risk maturity criteria fulfillment method. Categories for the data analysis are: commitment, resource allocation, implementation, quantitative measurement, and documents. Data collected from the questionnaire will be categorized and calculated in percentages as scores for commitment, resource allocation, and implementation aspects. These results are cross-checked with interview results to recheck and deepen risk management’ processes and activities. For quantitative measurement, the percentage was taken from interview result regarding existence of measurement needed and its implementation. The secondary research was used to gain percentages of documents aspects through completion of required documents availability in risk management. The findings indicate that the risk maturity level of XYZ Bank is on level 5, which is in Optimizing level, with a total score of 90.90 out of 100 from the weighting method and 93.33 out of 100 from the risk criteria fulfillment method. Therefore, suggestions given to the XYZ Bank are to maintain their ongoing risk management implementation in their programs, trainings, tests, and evaluation, along with additional intensive learning for employees who are still lack of risk knowledge and utilize more on existing potential improvement facilities to increase employee’s awareness in risk knowledge development.